2006
DOI: 10.1074/jbc.m605260200
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Functions and Estrogen Receptor-dependent Nuclear Translocation of Pleiotropic Human Prohibitin 2

Abstract: Proteins with multiple cellular functions provide biological diversity to eukaryotic cells. In the current studies, we identified the mitochondrial functions of human prohibitin 2 (PHB2), which was initially identified as a repressor of estrogen-dependent transcriptional activity. The mitochondrial complex of PHB2 consists of PHB1, voltage-dependent anion channel 2, adenine nucleotide translocator 2, and the anti-apoptotic Hax-1, which is a novel binding partner for PHB2. RNA interference-mediated knockdown of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
215
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(235 citation statements)
references
References 39 publications
20
215
0
Order By: Relevance
“…In HeLa cells, mitochondrial PHB2 translocates to the nucleus in the presence of ERa and E2 (ref. 32). These findings suggest the involvement of mammalian PHB2 protein in the regulation of transcription in the nucleus.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…In HeLa cells, mitochondrial PHB2 translocates to the nucleus in the presence of ERa and E2 (ref. 32). These findings suggest the involvement of mammalian PHB2 protein in the regulation of transcription in the nucleus.…”
Section: Discussionmentioning
confidence: 70%
“…These data suggest that PHB2 can inhibit mitochondrial fission and apoptosis, and PHB2 may antagonize myocardial injury. Previous reports have shown that loss of prohibitins results in the fragmentation of the mitochondrial network in HeLa cells and MEFs 13,14 . The mitochondrial fragmentation of PHB2-depleted MEFs strikingly resembles the mitochondrial morphology observed after OPA1 downregulation 14,27 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mitochondria, PHB2 interacts with Mdm12p (20) and sphingosine-1-phosphate (42), thereby regulating mitochondrial functions. In the nucleus, PHB2 physically interacts with the estrogen receptor (43) and brefeldin A-inhibited guanine nucleotide-exchange protein 3 (BIG3) (44), resulting in suppression of gene transcription and contributing to tumor growth inhibition (10). In the cytosol, PHB2 but not PHB1 binds Akt2 and reciprocally regulates Akt2 levels and muscle differentiation (12,45).…”
Section: Discussionmentioning
confidence: 99%